LEARNING PROCESS THROUGH INTERACTION EDUCATIVE IN ISLAMIC EDUCATION - Wahyu Hoerudin, Cecep; Yuliani, Yuliani (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Education plays a vital role in shaping individuals and society, and effective educational interaction is central to successful learning outcomes. Purpose: This study explores the learning process through educational interaction in Islamic education, focusing on the relationship between educators and students. The research highlights how effective interaction—whether direct or indirect—determines learning outcomes. Method: Using a qualitative descriptive approach, the study shows that teachers must employ appropriate strategies and methods to make learning engaging and effective. Result: The findings emphasize that educational interaction, as outlined in the Qur'an, plays a significant role in teaching and learning processes, influencing both cognitive and moral development in students. Conclusion: The study concludes that educational interactions, rooted in both traditional and interactive methods, are essential for achieving balanced learning outcomes, and that fostering these interactions can significantly enhance students’ spiritual and moral growth.